REVIEW ANALYSIS OF CLASS I NARCOTICS ABUSE SANCTIONS FOR YOURSELF ( Study Decision Number 707 PK/ Pid.Sus /2022) - Ferdinand Sembiring; Yasmirah Mandasari Saragih; Rahmayanti (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Indonesia is one of the countries with draft​ Supremacy Law that is above law​ everything , law made as superiority the rules of the game in a country or can be called a rule of law ( rechtsstaat ). Therefore​ Therefore , Indonesia is a law - abiding country the rules are stated in regulation applicable laws in Indonesia . Writing This use study law descriptive , which is in study This writer use type study juridical normative use method Research data collection References. Study This For know the problem consideration Panel of Judges at Binjai District Court in implement the Circular Letter Supreme Court Number 4 of 2010 , analysis Review Return To Penalty Abuse Narcotics Group I Share Self Alone ( Study Decision Number 707 PK/ Pid.Sus /2022) . Reviewed from Constitution Number 35 of 2009 in conjunction with Circular Letter The Supreme Court Number 4 of 2010 ( Analysis Decision Number 707 PK/ Pid.Sus /2022. Based on results research and discussion so obtained picture , that consideration Panel of Judges at Binjai District Court in apply letter circular court great number 4 of 2010 inside decision level First only based on accusations and demands prosecutor without consider return fill letter circular court great number 4 of 2010 concerning placement abusers , abuse victims and addicts narcotics into the rehabilitation medical and rehabilitation social causes​ injustice decision for abuse narcotics group I for self Alone. That application the sentence carried out by the convict is decided by the Binjai District Court there is mistake so that Supreme Court in matter application review return is done convict decide convict do abuser narcotics group I for himself Alone .